Depressive Symptoms Enhance Stress-induced Inflammatory Responses - Fagundes, Christopher P. (2012)
Depression is a risk factor for morbidity and mortality, and immune dysregulation may be partially responsible for this link. Proinflammatory cytokines such as interleukin 6 (IL-6) are reliable predictors of quality of life, morbidity, and many causes of mortality. The current study evaluated relationships between depressive symptoms, as assessed by the CES-D, and stress-induced inflammation. The participants, 138 healthy adults, were evaluated at rest, and after a standardized laboratory speech and mental arithmetic stressor. Compared with individuals with fewer depressive symptoms, those with more depressive symptoms produced more IL-6 in response to the stressor, as well as significantly higher levels of IL-6 both 45 minutes and 2 hours after the stressor. These findings add to our emerging understanding of the complex interactions among stress, depression, and immune dysregulation, and provide one potential pathway to explain relationships between depressive symptoms and disease.